Lussazioni del carpo - Rampoldi, M.; Antonietti, G.; piccioli, A. (Lo Scalpello - Journal, 2018)
CARPAL INSTABILITIES Carpal instabilities are uncommon and challenging lesions resulting from high energy traumas, often affecting young patients. They can result in significant morbidity and disability if inadequately treated. Their anatomy is complex and some aspects of their pathomechanisms still need to be clarified. The diagnosis is often difficult and can be missed in up to 25% of cases, especially in pure ligamentous lesions. Treatment must be prompt, and open anatomic reduction of any carpal malalignment is essential for a successful outcome.